ДОСЛІДЖЕННЯ КОНВЕКТИВНОГО СУШІННЯ ГЛИВИ ЗВИЧАЙНОЇ - Petrova, Z.; Samoilenko, K. (Institute of Engineering Thermophysics of NAS of Ukraine, 2025)
The kinetics of dehydration of cultivated common oyster mushroom (Pleurotus ostreatus) by convective method was studied and rational operating parameters were established to reduce the process duration. The dependence of the physical and chemical properties of oyster mushroom on the temperature of the heat carrier was investigated. The restorative properties of dried mushroom powder were determined.